Zavarovanje terjatev z vrednostnimi papirji - Juhart, Miha (Pravni letopis, 2013)
Collateral with pledge of securities is an important form of collateral in modern financial transactions. Especially stocks and bonds are very suitable object of pledge. In Slovenia stocks and bonds are obligatory issued as dematerialized security. The creditor obtains his right of pledge on dematerialized securities by the registration in the central register of dematerialized securities.Therefore the main legal issue is the execution of the creditors right to reimbursement. In the case of paper (materialized) securities the creditor executes the sale of the pledged securities in the same way as movable property. The execution of pledge on dematerialized securities is especially regulated in the Book Entry Securities Act. Special rules apply for the financial collaterals subject to the Financial Collaterals Act. In case of the financial collaterals the creditor has an additional opportunity to seize the securities instead of executing the sale. In Slovenian Law the rules of pledge strictly prohibit the so called Lex Commisoria Clause. By the financial collaterals there are some exemptions from this strict rule. However, even in this case the creditor shouldn't be enriched by the execution of the collateral.
Keywords: dolgovi; terjatve; vrednostni papirji; zavarovanje